Decreased Time from 9-1-1 Call to PCI among Patients Experiencing STEMI Results in a Decreased One Year Mortality. (2nd November 2018) - Studnek, Jonathan R.; Infinger, Allison; Wilson, Hadley; Niess, Gary; Jackson, Patrick; Swanson, Doug
ABSTRACT: Background: The impact on mortality due to prompt recognition of ST-segment Elevation Myocardial Infarction (STEMI) patients by EMS has not been well described. The objective of this study was to describe the association between the time interval, 9-1-1 call to percutaneous intervention (PCI), and mortality at one year.Methods: This retrospective analysis included patients that were transported by EMS as a "code STEMI" and underwent PCI. Total time from 9-1-1 call to PCI was calculated for each patient and was the independent variable of interest. Each patient's mortality status at one year was the outcome variable, collected by querying medical records and the national death index. Confounding variables were abstracted from hospital records. Logistic regression was conducted to determine the likelihood of survival given differences in time to PCI.Results: A total of 550 patients were included in the analyses of which 68% were male with an average age 59.8 (SD 12.8). Mean reperfusion time was 81.8 min (SD 20.0) and was significantly lower in patients alive at one year (80.8 min, SD 19.7) vs. deceased at one year (93.9 min, SD 19.6), respectively. Odds of survival at one year decreased by 3% (OR 0.97; 95% CI 0.96–0.99) for every one minute increase in time to PCI. This relationship practically represents a 30% increase in mortality for every 10 minute delay from 9-1-1 call to PCI.Conclusion: The model produced suggests that a linear relationship exists between time to PCI and mortality in the prehospital environment with the probability of survival decreasing significantly as time to PCI increases.